Health of migrants during the disease while staying in Poland - Monika Pierzak; Wiktoria Bielecka (Kazimierz Wielki University, 2018)
The phenomenon of emigration has been the subject of discussion and reflection for many years. The connection between emigration and deterioration of health condition is increased in the current situation of the wave of emigration, because the most popular and most commonly used strategy of migration is the shuttle. This kind of emigration concept often results in disturbances in the functioning of the emigrant in various social structures, in the country from which he comes as well as in the country of emigration, which is not without significance on the psychophysical state of the person and also his relatives. Medical problems typical for expatriates usually arise from the neglect of prevention, scarcity or limited access to health care, tiring and burdensome physical work, experiencing enormous psychological costs as a result of separation from loved ones and awareness of loneliness in a culturally unknown environment.